Incidence, morbidity and mortality of hip fractures over a period of 20 years in a health area of Southern Spain - Marta M Rey-Rodriguez; MA Vazquez-Gamez; Mercè Giner; Fernando Garrachón-Vallo; Luis Fernández-López; Miguel Angel Colmenero; María-José Montoya-García (BMJ Open)
Objective To evaluate the incidence of osteoporotic hip fracture in the Macarena Health Area (Seville).Setting and participants This was a prospective observational study that collected all osteoporotic hip fractures that occurred between March 2013 and February 2014 at the Clinical Unit of Traumatology and Orthopaedics. All cases collected during the first 6 months of the study were followed for 1 year after the occurrence of the event.Outcome measures We evaluated the incidence of osteoporotic hip fractures in the Macarena Health Area (Seville) from 1 March 2013 to 28 February 2014, and we compared the incidence with that in 2 previous studies carried out with the same methodology in 1994 and 2006. Furthermore, we calculated the morbidity and degree of disability 1 year after the fracture occurred and determined mortality and the associated factors.Results The overall incidence was 228 per 100 000 individuals/year (95% CI 204.5 to 251.6), and the incidence was higher in women than in men. In women, the incidence rate decreased in all age groups over time, while in men, the incidence rate increased. The mortality rate 1 year after the episode was 27.2%. The factors associated with overall mortality were a body mass index below 25 kg/m2, renal failure and low plasma proteins.Conclusions Our results show a high incidence of osteoporotic hip fracture that is increasing in men, and in men it is associated with a higher mortality than in women. There is room to improve the modifiable factors associated with mortality and the available rehabilitation interventions to reduce the disability associated with these fractures.